â€œLabor Migration Jagoi Babang Districts to Malaysiaâ€ - B01111010, Arianto Koneng (Jurnal Pembangunan dan Pemerataan, 2016)
West Kalimantan is one of the provinces in Indonesia which directly borders withneighboring countries Malaysia. Therefore, many people who take advantage of these conditionsto look for jobs in Abroad.The title of this research is "Labour Migration District of Jagoi Babang to Malaysia".The research aims to determine the alleged relationship Wages, Education, Employment Type ina Destination and Type of Work in the Region of Origin. The research location in District JagoiBabang Bengkayang. This study used qualitative analysis techniques.The analysis showed that the relationship wages, education, job type in the destinationarea and type in the Work Area of origin was found differences in the nominal amount of suchwages due to the rupiah. The results showed that after migrating to Malaysia standards of livingfor the better.Keywords: Labor and Migration